Student perceptions' of the educational environment in the midst of curriculum change (Medical Journal of Indonesia, 2008)
The Faculty of Medicine University of Indonesia underwent a major curriculum reform in 2005. There is a necessity to evaluate the new curriculum's educational environment, as a part of the curriculum evaluation. In June 2007, the DREEM (Dundee Ready Education Environment Measure) was administered to 210 second year students with an innovative curriculum and 259 third year students with the more traditional curriculum, to measure the students' perceptions of the educational environment. One of the most significant differences between the perceptions of the two groups is that there are less cheating problems in the second year, but the third year is better timetabled. The almost similar profiles indicate that the new curriculum's educational environment has not improved significantly. It is related with problems in managing and organizing the new curriculum's detail aspects. The institution needs to re-evaluate the perceptions of the educational environment when the curriculum is more internalised. (Med J Indones 2008; 17: 57-63) Keywords: educational environment, DREEM, curriculum change, curriculum evaluation